The dilemmas of development work : Ethical challenges in regeneration - Hoggett, Paul (Book collections on Project MUSE., 2009)
This book, written by three well-known educators and researchers in the social policy and development field, explores the ways in which front-line professionals, working with communities, identify and address the dilemmas inherent in the current policy context.